Study of biodiesel blends on emission and performance characterization of a variable compression ratio engine - Chavan S.B.; Kumbhar R.R.; Kumar A.; Sharma Y.C. (My University, 2025)
This study explores the emission of different pollutants using different blends in a variable compression ratio (VCR) engine. Biodiesel synthesized from Jatropha oil using a heterogeneous catalyst was investigated for emission analysis on a single-cylinder VCR engine with various blending ratios as well as load. Blends (biodiesel + diesel) of JB00, JB10, JB20, JB30, and JB100 were prepared at 40 °C. The emission parameters, such as nitrogen oxides (NOx), carbon monoxide (CO), and hydrocarbon (HC), were studied and compared to diesel fuel. Results showed that, among the blends prepared from methyl ester of Jatropha, JB30 shows reduction in emissions of CO and HC up to 43 and 50%, respectively, with an increment of NOx emission up to 20% at the lowest load and compression ratio (CR) of 15. The optimum parameter for the lowest pollutant emission for JB30 was found with a load of 6 kg at CR of 15. © 2015 American Chemical Society.